การรณรงค์ทางการเมืองบนโลกออนไลน์เพื่อสนับสนุนการเปลี่ยนผ่านอำนาจ: กรณีศึกษาเฟซบุ๊กเพจ "ล้านชื่อต้านล้างผิด" "The mettad" และ "ลุงตู่ตูน"ในช่วงการเลือกตั้ง 2562 - ทัตเทพ ดีสุคนธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This thesis focuses on the political campaign from the Facebook pages "Anti-Amnesty","THE METTAD", and "Super Lungtoo" presented themselves as anonymous Facebook pages or controlled by unidentified owners who continuously produce content to support the transition of power of Prayut’s government and attack the political opponents during the 2019 General Electionto answer the main research question: These Facebook pages have characteristics, roles, and significance in which are similar or different from the government s political campaigns disseminated in other channels. The study has been conducted qualitatively through the content analysis and document research to explore the formats and contents that these 3 pages used in campaigning, the way of Facebook users commented on the pages, and the contents that made political effects.The study found that although these 3 Facebook pages often used a presentation format that links with today’s social media communication culture, most of the presented content was associated with the Hegemony of Thai society: The Nation, the Religion, and the Monarchy, differing from the other campaigns that often supported the government by presenting their policies and success without attacking the opponents. Besides, most Facebook users usually gave supportive comments to the page’s contents, causing these anonymous pages to become an echo chamber where people who support Prayut’s government are brought together without spreading contents to the other groups. However, some of the contents shared by anonymous Facebook pages to attack the opponents were not only mentioned in the online echo chamber, but also made the political effects via public figure s interviews and litigations. As a result, it could show a power of the anonymous Facebook page which was one of the mechanisms that worked behind the 2019 General Election campaigns and may be more intensely applied in the future elections.